2017
DOI: 10.7172/2353-6845.jbfe.2017.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Inflation and Public Debt Reversals in the G7 Countries

Abstract: This paper investigates the impact of low or high infl ation on the public debt-to-GDP ratio in the G-7 countries. Our simulations suggest that if infl ation were to fall to zero for fi ve years, the average net debt-to-GDP ratio would increase by about 5 percentage points during that period. In contrast, raising infl ation to 6 percent for the next fi ve years would reduce the average net debtto-GDP ratio by about 11 percentage points under the full Fisher effect and about 14 percentage points under the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 15 publications
(11 reference statements)
6
21
0
Order By: Relevance
“…The result was a positive mean correlation of 0.36 between the two variables for 15 OECD-countries in the period [1973][1974][1975][1976][1977][1978][1979][1980][1981][1982]. In contrast, the correlation was negative (-0.19) during the period 1983-1989. Akitoby et al [2014, investigated by the use of simulation for the G7-countries and found that higher inflation could help reduce the public debt-to-GDP ratio.…”
Section: Brief Overview On Empirical Studiesmentioning
confidence: 99%
“…The result was a positive mean correlation of 0.36 between the two variables for 15 OECD-countries in the period [1973][1974][1975][1976][1977][1978][1979][1980][1981][1982]. In contrast, the correlation was negative (-0.19) during the period 1983-1989. Akitoby et al [2014, investigated by the use of simulation for the G7-countries and found that higher inflation could help reduce the public debt-to-GDP ratio.…”
Section: Brief Overview On Empirical Studiesmentioning
confidence: 99%
“…This study seems to be more significant for the region of South Mediterranean, these countries made many reforms in the way of capital flows liberalization and the same period is accompanied with a rise on their external debts 1 . This paper seeks to add to the current literature on the association between account liberalization and external debt by examining a panel data for 8 south Mediterranean countries (SMCs) from 1971 to 2015.…”
Section: Introductionmentioning
confidence: 78%
“…We take two approaches to address our main question. First, we use a simulation approach, updating and expanding a previous study based on an extension of the standard debt dynamics equation (Akitoby et al, 2014), assuming that an inflation shock affects public debt-to-GDP ratio only through outstanding fixed-rate, long-term debt. Second, we adopt an estimation approach based on the local projection method, to estimate impulse response functions to inflation shocks.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1(a) summarizes recent studies on the effects of inflation shocks on public debt using simulations. The closest approach to ours is Akitoby et al (2014), where the effects of a persistent inflation shock that raises inflation to 6 percent for the next five years on the public debt-to-GDP ratio is simulated using the IMF's World Economic Outlook (WEO) data for G7 countries. Compared to them, we use updated WEO data and expand sample countries.…”
Section: Introductionmentioning
confidence: 99%